Tinjauan Fiqih Muamalat Terhadap Praktik Jual Beli Kredit Hp Melalui Aplikasi Online Kredivo - Zaidan Nashih Ulwan; Abdullah Fahmi Al Kayyisi; Hafizd Dhafa Anudra; Muhibban (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
The increasing use of online applications in trading practices, particularly the purchase of mobile phones on credit through the Kredivo platform, raises questions about the compatibility of such practices with the principles of Islamic commercial jurisprudence (fiqh muamalat). This study aims to analyze and evaluate the practice of purchasing mobile phones on credit via Kredivo from the perspective of fiqh muamalat. The method used is a literature study with qualitative analysis of fiqh sources and relevant regulations, as well as interviews with fiqh scholars and practitioners in the financial sector. The results of the study indicate that the practice of purchasing mobile phones on credit through Kredivo aligns with some aspects of fiqh principles; however, there are elements that may potentially involve usury (riba) and uncertainty (gharar), which require attention. The conclusion of this study underscores the importance of understanding and applying the principles of fiqh muamalat in online transactions to ensure that such practices comply with Islamic law.